THE EFFECT OF PESTICIDES ON THE STATE OF THE MICROVASCULATURE AND TISSUE STRUCTURES OF THE OVARY - Khozhanazarova Saulekhan Jubatirovna; Shamsiyev Shakhzod Jabbor ugli (Scholar Express Journals, 2022)
The aim of the study is to study the postnatal morphogenesis of tissue structures and intraorganic vessels of the ovary of the offspring, under conditions of chronic toxic effects of the “Vantex” pesticide on the mother's body. Material and research methods. The experiments were carried out on white outbred rats. The animals were divided into 2 groups of 30 individuals each: group 1 (control) - intact animals, i.e. rat pups born from intact mother rats, group 2 - rats, which, in order to create a model of chronic pesticide poisoning Results: It has been established that chronic intoxication of the mother with the “Vantex” pesticide negatively affects the processes of postnatal growth, development and formation of the vascular tissue structures of the reproductive organs, in particular the ovary of the offspring, i.e. The pesticide “Vantex” has a reproductively toxic chemical. Chronic intoxication of the mother with the pesticide "Vantex" leads to the development of inflammatory-reactive changes in the vascular tissue structures of the ovaries in the early periods of postnatal development of the offspring
Keywords: chronic intoxication with pesticides; mother-offspring; ovary; tissue